2007
DOI: 10.1007/s11604-007-0152-4
|View full text |Cite
|
Sign up to set email alerts
|

High-dose-rate brachytherapy for previously irradiated patients with recurrent esophageal cancer

Abstract: These data suggest that HDR brachytherapy is an effective and safe treatment for patients with recurrent esophageal cancer after external radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…23) Recently, Nonoshita et al reported a curative high-doserate brachytherapy with or without chemotherapy for six previously irradiated patients with recurrent superficial esophageal cancer; no severe complications were observed, and local control was achieved in 5 of 6 patients. 24) In our curative group, the patients had a T1-2 tumor, a tumor size of less than 4 cm, and few severe complications; only one patient had a Grade 3 esophageal perforation, and 10 (91%) of 11 patients had an objective response and the median overall survival time was 19 months. We found that in the patients of the curative group, our multimodal approach including re-irradiation is feasible with acceptable toxicity and a potential value of a promising treatment for the longterm survival of some patients.…”
Section: Discussionmentioning
confidence: 81%
“…23) Recently, Nonoshita et al reported a curative high-doserate brachytherapy with or without chemotherapy for six previously irradiated patients with recurrent superficial esophageal cancer; no severe complications were observed, and local control was achieved in 5 of 6 patients. 24) In our curative group, the patients had a T1-2 tumor, a tumor size of less than 4 cm, and few severe complications; only one patient had a Grade 3 esophageal perforation, and 10 (91%) of 11 patients had an objective response and the median overall survival time was 19 months. We found that in the patients of the curative group, our multimodal approach including re-irradiation is feasible with acceptable toxicity and a potential value of a promising treatment for the longterm survival of some patients.…”
Section: Discussionmentioning
confidence: 81%
“…It was not known whether re-irradiation definitely increased the risk of esophageal perforation. The treatment options after local recurrence includes surgery, chemotherapy and RT [ 15 17 ], and data about patients receiving re-irradiation is rare [ 18 ]. For various reasons, patients with local recurrence in our study did not receive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Nonoshita et al [12] reported 6 patients with recurrent esophageal cancer after external radiotherapy (median dose, 60 Gy). T stage at the time of primary radiotherapy and recurrence was T1 in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the literatures, the median overall survival after re-RT of recurrent esophageal cancer after primary definitive radiotherapy was 6.5-30.0 months [11,12] (Table 4). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation